The Akiba Mashinani Trust, Kenya: a local fund's role in urban development. (April 2018) - Weru, Jane; Okoyo, Omondi; Wambui, Mary; Njoroge, Patrick; Mwelu, Jacinta; Otibine, Evans; Chepchumba, Ann; Wanjiku, Regina; Wakesho, Tabitha; Njenga Maina, John Pius
This paper describes the funding and financial services provided by the Akiba Mashinani Trust (AMT) to support the Kenyan Homeless People's Federation (Muungano wa Wanavijiji). Muungano is a federation of autonomous savings groups with over 60, 000 members from informal settlements across Kenya. Savings are critical because they enable wealth accumulation, demonstrate the capacity of the community to repay loans and hence leverage additional resources, and build social capital among members. AMT is able to use these savings as seed capital for revolving funds at the community, city and national scales. The funds offer informal settlers a range of financial products, including community project loans, which allow savings groups to finance social housing, sanitation and basic infrastructure in an affordable way. Therefore, unlike formal banking and microfinance institutions, AMT positions its financial services within a broader effort to improve the physical and social fabric of urban informal settlements. The experiences of Muungano and AMT demonstrate the catalytic impact of establishing appropriate financial services geared towards low-income groups – and crucially, how the savings of low-income people can leverage government resources to achieve more inclusive cities.